Esporre «integralmente la dottrina» e regolarsi «secondo l’opportunità» - Vian, Giovanni (JoMaCC, 2022)
The Italian Risorgimento process saw the Apostolic Penitentiary, generally accustomed to operating with great confidentiality, rising to a prominent ‘public’ role. It was in the context of the Roman Question that the Holy See had to deal with the introduction of the new Italian Penal Code (commonly called ‘Zanardelli Code’), which was approved in June 1889 and came into force at the beginning of the following year. This article offers a reconstruction of the reaction of the Apostolic Penitentiary and the Holy See to the publication of the Code.